2023
DOI: 10.1002/jsfa.12530
|View full text |Cite
|
Sign up to set email alerts
|

Effects of optimized nitrogen fertilizer management on the yield, nitrogen uptake, and ammonia volatilization of direct‐seeded rice

Abstract: BACKGROUND Direct‐seeded rice has been developed rapidly because of labor savings. Changes in rice cultivation methods put forward new requirements for nitrogen (N) fertilizer management practices. Field experiments with five different fertilizer ratios of basal, tillering and panicle fertilizer, namely N1 (10:0:0), N2 (6:2:2), N3 (4:3:3), N4 (2:4:4) and N5 (0:5:5), were conducted to investigate the effects of different N fertilizer management practices on yield formation, N uptakes, and ammonia (NH3) volatili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Ma et al. (1992) found that the main source of nitrogen in the regenerating tillers was the transfer of nitrogen from rice stubble, and the nitrogen contribution of the main crop bud-promoting fertilizer was small. Lin et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ma et al. (1992) found that the main source of nitrogen in the regenerating tillers was the transfer of nitrogen from rice stubble, and the nitrogen contribution of the main crop bud-promoting fertilizer was small. Lin et al.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the decline in root function during the grainfilling stage of rice, the efficiency of nitrogen absorption and utilization is often low . Ma et al (1992) found that the main source of nitrogen in the regenerating tillers was the transfer of nitrogen from rice stubble, and the nitrogen contribution of the main crop budpromoting fertilizer was small. Lin et al (2015) found that the export percentage and apparent conversion rate of nitrogen from the stem and sheaths of the main crop to the ratoon crop were 37%-49% and 29%-54%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, the rice planting area is approximately 162 million hectares, accounting for 11% of the world's arable land, and approximately 758 million tons of rice are produced annually 4 . However, with social and economic development, labor and water resource shortages and environmental deterioration have posed great challenges to traditional transplanted rice production methods 5 . The development of resource‐saving, environment‐friendly, and lightly simplified rice production methods is an inevitable trend in current rice production 6 …”
Section: Introductionmentioning
confidence: 99%
“…4 However, with social and economic development, labor and water resource shortages and environmental deterioration have posed great challenges to traditional transplanted rice production methods. 5 The development of resource-saving, environmentfriendly, and lightly simplified rice production methods is an inevitable trend in current rice production. 6 At present, there are two main methods of rice cultivation: transplanted and direct-seeded, with direct-seeded rice being divided into dry direct-seeded rice (DSR) and wet direct-seeded rice (WSR) according to the moisture condition of the land at the time of sowing.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive nitrogen fertilizer leads to the absorption of excess nitrogen by rice, resulting in nitrogen waste in the soil [6]. On the other hand, insufficient nitrogen fertilizer affects rice photosynthesis, which results in reduced yield [7,8]. While higher nitrogen fertilizer input can help to increase rice yield, it reduces nitrogen use efficiency, adversely affecting biodiversity, human health, and climate and posing a significant challenge to the nitrogen cycle [9,10].…”
Section: Introductionmentioning
confidence: 99%